A fast iterative method for identifying the radiogenic source for the helium production-diffusion equation. Issue 1 (2nd January 2022) - Zhang, Zhengqiang; Zhang, Yuan-Xiang
ABSTRACT: In this paper, we consider an inverse source problem for the helium production-diffusion equation. That is to determine a space-dependent source term in the helium production-diffusion equation from a noisy final data. Since the problem is ill-posed, we propose an effective iterative scheme to deal with the problem. More specifically, we use an acceleration technique to speed up a simple iterative scheme. We also give two kinds of convergence rates by using an a priori and a posteriori regularization parameter choice rule, respectively. Numerical examples are presented to illustrate the validity and effectiveness of the proposed method.